Sex-specific association between gut Faecalibacterium prausnitzii and hypertension in male individuals - Fu, Jing; Bu, Guosen; Aimaier, Salamaiti; Yang, Yuchun; Bao, Zhen; Wulasihan, Muhuyati (Frontiers in Microbiology, 2025)
ObjectiveWhile gut microbiota (GM) dysbiosis has been implicated in hypertension, the sexassociated microbial signatures and their underlying mechanisms remain poorly understood, particularly in populations living in unique geographical and climatic conditions.DesignThrough an integrated approach combining 16S rRNA sequencing, shotgun metagenomics, and serum metabolomics, we systematically investigated the sex-associated characteristics of the gut microbiota in hypertension among a cohort of 200 participants from Xinjiang.MethodsAn initial cohort analysis identified Faecalibacterium as a male-associated biomarker for hypertension. Subsequent species-level characterization revealed that Faecalibacterium prausnitzii (F. prausnitzii) showed significant negative correlations with systolic blood pressure (SBP). This male-specific association was consistently observed across both 16S rRNA sequencing and shotgun metagenomic datasets. Then, our integrated analysis suggested a potential pathway through which F. prausnitzii may be linked to systolic blood pressure in male individuals, with N-phenylacetylglutamine (PAGln) identified as a potential mediating metabolite.ConclusionOur study establishes a microbe–metabolite–clinical trait axis in the pathophysiology of sex-associated hypertension and significantly advances our understanding of sex-driven host–microbe interactions.